Colonel Roosevelt - Morris, Edmund (Random House Trade Paperbacks, 2011)
Presents a chronicle of the last ten years of Theodore Roosevelt's life to cover his African safaris, return to public life, involvement with the Progressive movement, campaign for president in 1912, and various brushes with death.